2016
DOI: 10.1007/s10554-016-0838-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of systolic left ventricular function with speckle-tracking echocardiography in adult patients with repaired aortic coarctation

Abstract: Despite successful aortic coarctation (CoA) repair, systemic hypertension often recurs which may influence left ventricular (LV) function. We aimed to detect early LV dysfunction using LV global longitudinal strain (GLS) in adults with repaired CoA, and to identify associations with patient and echocardiographic characteristics. In this cross-sectional study, patients with repaired CoA and healthy controls were recruited prospectively. All subjects underwent echocardiography, ECG and blood sampling within 1 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
3
18
1
1
Order By: Relevance
“…Jashari et al reported more impaired longitudinal strain in CoA patients with LV hypertrophy, as confirmed by other studies [ 9 , 27 , 28 , 31 ]. The myofiber orientation changes throughout the myocardium, with a predominantly longitudinal orientation in the endomyocardium [ 10 , 27 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Jashari et al reported more impaired longitudinal strain in CoA patients with LV hypertrophy, as confirmed by other studies [ 9 , 27 , 28 , 31 ]. The myofiber orientation changes throughout the myocardium, with a predominantly longitudinal orientation in the endomyocardium [ 10 , 27 ].…”
Section: Discussionsupporting
confidence: 73%
“…Delayed repair of CoA may induce a maladaptive response of the LV, resulting in adverse outcome later in life [ 12 ]. Age at the time of repair has therefore been identified as a predictor for impaired longitudinal strain [ 31 ]. In addition, the set point of the renin–angiotensin–aldosterone system is defined in neonatal life [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be time of exposure to maladaptive fibrosis, myocyte degeneration, and myocyte loss 14 . We did not find any correlations between GLS and the other variables, such as arm‐leg gradient, isthmus gradient, hypertension, 37 or LV mass index 17 …”
Section: Discussioncontrasting
confidence: 58%
“…These data suggest that CoA leads to subclinical LV dysfunction, which is not detectable by conventional echocardiography, with progressive improvement after stenting. Similarly, impaired LV GLS in patients with untreated CoA has also been demonstrated by several authors, employing different technologies including magnetic resonance imaging, tissue Doppler, and 2D and 3D speckle tracking 10,14,17,19,20,35 …”
Section: Discussionmentioning
confidence: 60%
“…Actualmente se conoce que la FEVI es un marcador subóptimo de disfunción ventricular sistóli-ca en etapas incipientes de daño miocárdico. El Speckle Tracking es una técnica sofisticada de ecocardiografía que proporciona una evaluación cuantitativa del movimiento del tejido miocárdico, independientemente del ángulo y la geometría ventricular, que permite detectar la disfunción miocárdica subclínica del VI [10][11][12][13] . El objetivo de este estudio fue buscar la presencia de disfunción sistólica temprana del VI en pacientes adultos con CoAo y HAS comparados con pacientes hipertensos sistémicos sin CoAo y controles sanos, mediante la técnica ecocardiográfica de Speckle Tracking.…”
Section: Introductionunclassified